IDENTIFICATION AND PARTIAL CHARACTERIZATION OF CRUDE EXTRACELLULAR ENZYMES FROM BACTERIA ISOLATED FROM SHRIMP WASTE PROCESSING - Chasanah, Ekowati; Ali, Mahrus; Ilmi, Miftahul (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Attention on chitin degrading enzymes has been growing since their ability to reduce the waste of shrimp/other crustaceans processing industries and converting them into value added products such as biologically active chitin and chitosan oligomer. Previous experiment found that KLU 11.16 isolate was one of the potential bacteria isolated from shrimp waste producing chitinolytic enzymes including chitosanases. A study on the identification of KLU 11.16 extracellularcrude enzyme was carried out by cultivating the bacteria on chitin medium. Due to the wide application of chitosanase, the characterization of the crude chitosanase was carried out after an identification of the enzymes secreted. Based on assessment using zymogram technique, this bacteria secreted a mixed extracellular chitinolytic enzyme and other hydrolytic enzyme. The crudechitinolytic enzyme degraded 85% deacetylated (DA) better than 100% DA chitosan, and slightly degraded glycol chitin, indicating that KLU 11.16 secreted chitosanases and chitinases enzyme. In addition to the chitinolytic enzyme, the bacteria also secreted protein and carbohydrate degrading enzymes when running at SDS-PAGE enriched with casein, soluble starch and CMC substrates.Crude chitosanases enzyme was performed well at pH 6 and temperature of 300C, and the activity can be increased by addition of 1 mM Fe 2+ in form of chloride salt. Addition of detergent, i.e1mM of Triton X-100 and SDS slightly decreased the activity. Future application of the crude chitosanase from KLU 11.16 was on producing chitosan derivative such as chitosan oligomer using substrateof 85% DA chitosan, which is more digestable by other enzymes secreted by KLU 11.16